Evaluation of the Effects of Monosodium Glutamate Overconsumption on the Functions of the Liver, Kidney, and Heart of Male Rats: The Involvement of Dyslipidemia, Oxidative Stress, and Inflammatory Responses - Heba M. Abdou; Amel H. El-Gendy; Rania Gaber Aly; Mekky M. Abouzied; Heba M. Eltahir; Sultan S. Al thagfan; Saber M. Eweda (Journal of Xenobiotics, 2025)
The excessive intake of monosodium glutamate (MSG) increases its cellular levels in different organs and induces organ toxicity. The current study aims to investigate the metabolic changes and possible causes of hepatic, renal, and cardiac toxicity induced by MSG overconsumption. Thirty adult male rats were randomly allocated into five groups: control, MSG0.8, MSG1, MSG2, and MSG3, which were orally treated with a daily oral dose of saline, 0.8, 1, 2, and 3 g MSG/kg BW, respectively, for eight weeks. The hepatic, renal, and cardiac biochemical markers; lipid profile; glucose; electrolytes; iNOS; α-KGD; oxidative stress; and inflammatory markers were investigated. The histopathological examination of hepatic and renal tissues was also performed. The results revealed MSG-induced hepato-renal and cardiac toxicity, as indicated by the changes in the biochemical markers and tissue architecture of these organs. The toxicity is observed in the form of dyslipidemia, oxidative stress (increased MDA and NO and decreased GSH, SOD, CAT, and GST), and inflammatory responses (increased TNF-α and IL-6). The histopathological changes in liver and kidney architecture confirmed the obtained results. In conclusion, the MSG-induced hepatic, renal, and cardiac toxicity was dose-dependent, and awareness should be raised about the side effects of the overconsumption of MSG.